Evaluation of laboratory exams and symptoms of patients with molecular diagnosis (RT-qPCR) of COVID-19 admitted to an Intensive Care Unit in a Western Parana city (Research, Society and Development, 2021)
The pandemic triggered by COVID-19 has been plaguing the world since December 2019, without any known specific treatment, leading to nearly 3 million deaths worldwide. Its transmission occurs from person to person and its main symptoms are fever, dry cough and fatigue. The aim of this study was to analyze the prognosis of patients with SARS-CoV-2 admitted to an Intensive Care Unit in the West region of Parana, through hematological and symptomatological parameters, helping in the establishment of protocols and procedures. From the data obtained, there was a greater number of deaths among older patients (p=0,01), and the laboratory profile with the worst prognosis was with hematocritopenia, leukocytosis, lymphocytopenia, neutrocytosis and greater number of respiratory symptoms. There was no association between sex and death (p=0,13) or length of stay (p=0,36). Therefore, new studies can use these laboratory and symptomatological markers, as well as age, to assist in the pandemic medical routine.